EFFECT OF ROOT OF VETIVER GRASS AND THE SHEAR STRENGTH OF ROOT IN PERMEATED SOIL - Mohammad Noh, Noorasyikin (Journal of Engineering & Technological Advances, 2021)
Recently, bioengineering has been approached as one of the slope stabilizations techniques as it is inexpensive compared to the mechanical stabilization technique. However, numbers of slope failure still reoccur due to the limitation of the bioengineering technique knowledge. Proper bioengineering material and methods must be carefully selected to overcome the problem. The objectives of this research are to determine the physical and mechanical properties of soil with Vetiver Grass roots as well as the root properties of the Vetiver Grass since these grass types have been applied widely for slope stabilization. The physical properties of soil lab tests have been determined such as compaction test, Atterberg limits test and sieve analysis test. The mechanical properties of soil with and without root grasses have been carried out through the shear box test. For the identification of the root properties of Vetiver Grass, the root morphology and the diameter of the root has been identified. The results for the lab tests conducted showed that the soil with roots have a higher shear strength compared to soil without roots included with FOS (Factor of Safety) calculation proving that the soil with the aid of Vetiver Grass will be effective in retaining soil.